2018
DOI: 10.1111/joa.12897
|View full text |Cite
|
Sign up to set email alerts
|

How thyroid hormones and their inhibitors affect cartilage growth and shape in the frogXenopus laevis

Abstract: Understanding how skeleton changes shape in ontogeny is fundamental to understanding how its shape diversifies in phylogeny. Amphibians pose a special case because their jaw and throat skeleton consists of cartilages that are dramatically reshaped midway through life to support new feeding and breathing styles. Although amphibian metamorphosis is commonly studied by immersing larvae in thyroid hormones (TH), how individual cartilages respond to TH is poorly understood. This study documents the effects of larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 58 publications
(84 reference statements)
4
25
0
Order By: Relevance
“…Similar to what was reported for Xenopus (Rose & Cahill, ), the premetamorphic tadpoles of D. muelleri exhibit T4‐induced shape changes in the lower jaw decoupled from adjacent tissues. Specifically, the upper jaw articulation remains anterior to produce the observed prognathism (Figure ).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Similar to what was reported for Xenopus (Rose & Cahill, ), the premetamorphic tadpoles of D. muelleri exhibit T4‐induced shape changes in the lower jaw decoupled from adjacent tissues. Specifically, the upper jaw articulation remains anterior to produce the observed prognathism (Figure ).…”
Section: Discussionsupporting
confidence: 82%
“…In Xenopus , the differential responsiveness to exogenous THs for the lower jaw and ceratohyals become increasingly similar to the natural remodelling when the TH exposure is at older stages (Rose & Calhill, ). These authors demonstrated that high doses exposure of early stage tadpoles to TH can induce cartilage elongation and thinning in excess of what occurs naturally in Xenopus species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations